Current Studies in the Sociology of Religion - Kent R. Kerley (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The study of religion as an academic discipline is a rather recent development in colleges anduniversities in the United States and abroad. Although French sociologist Émile Durkheim wrote extensively about the role of religion in public life in the early 1900s, it was not until the 1960s that researchers from social science backgrounds, predominately sociology, began the formal, empirical study of religion as a social force that may impact a wide range of individual and societal outcomes. This special issue of Religions brings together scholars from around the world who use diverse methodologies to study the impact of religion on a broad range of outcomes. The issue thus provides a unique snapshot of current work being done in the sociology of religion. In these 18 articles, readers will find a great mix of data-driven studies (both quantitative and qualitative) and conceptual/review papers. The articles also reflect a diversity of authors, locations, topics, and faith traditions. I am pleased that many of the papers include undergraduate and graduate students as co-authors. These collaborations are important for maintaining the continuity of high-quality research over time.